'I've got lots of gaps, but I want to hang on to the ones that I have': the ageing body, oral health and stories of the mouth. Issue 6 (11th June 2020) - Warren, Lorna; Kettle, Jennifer E.; Gibson, Barry J.; Walls, Angus; Robinson, Peter G.
Abstract: The mouth may be presented and understood in different ways, be subject to judgement by others and, as we age, may intrude on everyday life due to problems that affect oral health. However, research that considers older people's experiences concerning their mouths and teeth is limited. This paper reports on qualitative research with 43 people in England and Scotland, aged 65–91, exploring the significance of the mouth over the lifecourse. It uses the concept of 'mouth talk' to explore narratives of maintaining, losing and replacing teeth. Participants engaged in 'mouth talk' to downplay the impact of the mouth, demonstrate socially appropriate ageing, and distance themselves from 'real' old age by retaining a moral identity and sense of self. They also found means to challenge dominant discourses of ageing in how they spoke about missing teeth. Referring to Leder's notion of 'dys-appearance' and Gilleard and Higgs' work on the social imaginary of the fourth age, the study illustrates the ways in which 'mouth talk' can contribute to sustaining a sense of self in later life, presenting the ageing mouth, with and without teeth, as an absent presence. It also argues for the importance of listening to stories of the mouth in order to expand understanding of people's approaches to oral health in older age.